Playing with density. The compass for Inward Development as a Problem-Oriented Methodology for Densification in Small- and Medium-Sized Communes. - Grams, Anita (vdf Hochschulverl., 2018)
The revised Swiss Spatial Planning Law, which came into effect in 2014, and the minimum strategy of "inward development before outward development" obligate municipalities to direct their spatial development toward existing, largely built-up spaces, and to coordinate building zone dimensioning across municipal boundaries. For many small- and medium-sized municipalities in Switzerland, this means changing thought patterns with regard to spatial planning practice. A major element of inward development is the constructional densification of existing settlement areas. However, especially in small- and medium-sized municipalities, densification is confronted with numerous problems, such as insufficient acceptance of dense building typologies, mobilisation obstacles for reserves secured under building law, and the lack of thought patterns concerning inward development. This is where the research in this volume sets in, leading to the hypothesis that inward development in the main settlement areas of Switzerland is possible, but that the existing formal instruments of spatial planning themselves are insufficient for this purpose.
Keywords: Bebauung; Raumentwicklung; Siedlungsplanung; Kommunalplanung; Verdichtung; Kleinstadt; Mittelstadt; Innenentwicklung